Time to Turn Up the Volume - van der Linde, Nadia (Anti-Trafficking Review, 2019)
I remember my first self-organised donor panel well. It was at the Global Social Change Philanthropy Conference in Washington, DC in 2013. I had just started work as the first coordinator of the Red Umbrella Fund—the newly established fund for and by sex workers. I organised a session that would clarify the distinction between sex work and human trafficking and emphasise the need to fund sex worker organising. We had a strong panel: an awesome sex worker activist, a knowledgeable academic, a passionate service provider, and a committed funder. I was, however, in for a rude awakening: even though the line-up was great, the audience was scarce. I thought to myself, if we can’t even get funders to show up and learn about sex workers’ rights, how will we ever meet the needs of sex worker organisations fighting for their basic human rights?